Flow cytometric-based detection of CD80 is a useful diagnostic marker of acute myeloid leukemia in dogs - Stokol, Tracy; Thomas, Sophie Isabella; Hoffman, Martha; Zhao, Shay (Frontiers in Veterinary Science, 2024)
CD80, a co-stimulatory molecule required for optimal T cell activation, is expressed on antigenpresenting cells, including monocytes and dendritic cells, in dogs and humans. We hypothesized that CD80 would be expressed on tumor cells in dogs from acute myeloid leukemia (AML) but not dogs with lymphoid neoplasms. We first evaluated the cellular staining pattern of a hamster anti-murine CD80 antibody (clone 16-10A1, ThermoFisher Scientific Cat# 17-0801-82, RRID: AB_469417) in blood and bone marrow aspirates from healthy dogs. Using flow cytometric analysis and examination of modified Wright's-stained cytologic smears of unsorted and flow cytometric or immunomagnetic bead-sorted leukocytes, we show that the antibody binds to mature and immature neutrophils and monocytes, but not lymphocytes or eosinophils, in blood and bone marrow. We then added the antibody to routine flow cytometric panels for immunophenotyping hematopoietic neoplasms in dogs. We found that the antibody labeled tumor cells in 72% of 39 dogs with AML and 36% of 11 dogs with acute leukemia expressing lymphoid and myeloid markers ("mixed lineage") but none of the dogs with B (n=37) or T (n=35) lymphoid neoplasms. A higher proportion of tumor cells in dogs with AML were labeled with the anti-CD80 antibody vs antibodies against other myeloid-associated antigens, including CD4 (36%, p = 0.003), CD11b (44%), CD11c (46%), CD14 (38%, p=0.006) and CD18 (59%, clone YFC118). In contrast, antibodies against CD11b and CD11c bound to tumor cells in 8-32% of the lymphoid neoplasms. We show that CD80, as detected by antibody clone 16-10A1, is a sensitive and specific marker for AML and would be useful to include in flow cytometric immunophenotyping panels in dogs. and monocytes) (2,3,9-12), CD61 (megakaryocytes) (3,12,13) and myeloperoxidase (an intracellular enzyme in neutrophils, eosinophils and monocytes) (9).